Plant species as ecological engineers of microtopography in a temperate sedge-grass marsh - Dušek, Jiří; Novotný, Jan; Navrátilová, Barbora; Mejdová, Markéta; Kokrda, Lukáš; Stellner, Stanislav; Kučerová, Andrea (Scientific reports, 2025)
In many temperate marshes, the surface microtopography is determined by specific growth forms of dominant wetland plants. The formation of long-lasting distinct tussocks by some Carex species represents a growth adaptation, which significantly changes the ecosystem and facilitates the survival of other wetland plants. Therefore, the gradual decline of such an ecosystem engineer may affect both species diversity and the surface microtopography of wetlands in the long term. Using in situ terrestrial laser scanning, we analyzed tussock characteristics in five different stands typical of a temperate sedge-grass marsh to determine potential microtopography changes due to an altered water regime. Tussocks of Carex acuta were different in 2D area, perimeter, height, and roundness. The distances among tussocks were similar and distributed evenly in all vegetation stands. The highest tussocks occurred in stands dominated by Carex acuta and in Carex acuta and Calamagrostis canescens mixture stands. Glyceria maxima and Acorus calamus significantly modified the height and the shape of tussocks in contrast to Calamagrostis canescens, which affects tussocks at least and uses them as habitats. The characteristics of tussocks in mixed stands were influenced by the growth characteristics of all co-occurring dominant plants (ecosystem engineers). Frequent shallow short-term flooding is necessary to maintain the current microtopography in the studied sedge-grass marsh as it promotes the dominance of tussock forming wetland plants and excludes ruderal or invasive terrestrial plant species.
Keywords: mokřady; Carex (rostlina); Terrestrial laser scanning (TLS); Poaceae; Wetland; Virtual reality; Point cloud; Sedges; Carex Plant; Wetlands; Ecosystem engineer; Ground-based LiDAR; Ecology; lipnicovité; ekosystém; Ecosystem